Psychosocial aspects of therapeutic donor insemination - Ansha Patel; P. S. V. N. Sharma; Pratap Kumar (Wolters Kluwer Medknow Publications, 2018)
The experience of delays in conception or possibility of remaining childless has the potential to create considerable psychological discomfort. In couples with severe male factor infertility, therapeutic intrauterine insemination using donor sperms (TDI) is offered as a treatment, second to in vitro fertilization using donor sperms. TDI is lucrative, less invasive, and a hopeful treatment. However, there are intricacies associated with it. Its immediate outcomes involve limited success rates, nonresponse, and chances of implantation failures, miscarriages, and multifetal pregnancies. Due to this, couples experience distress when they are advised to undergo three to six cycles of TDI in order to meet the expectations of having a baby. TDI has long-term issues on the triad comprising the "recipients," the "donors," and the "the children born out of TDI." Nevertheless, managing psychosocial needs for couples undergoing TDI and other treatments in Indian clinics are grey areas of the conventional treatment pathway. The present review expands on the psychological issues and needs in couples opting for TDI.